2007
DOI: 10.20502/rbg.v8i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Análise Multitemporal e Caracterização dos Processos Erosivos no Baixo São Francisco Sergipano.

Abstract: A erosão das margens do baixo curso do rio São Francisco é uma das causas mais visíveis das alterações na dinâmica do sistema fluvial e se destaca pela sua amplitude, ampla distribuição e conseqüências sócio-econômicas. O objetivo desse trabalho foi apresentar uma análise multitemporal dos processos erosivos no baixo curso do rio São Francisco, à jusante da UHE Xingo. Foram realizados estudos do comportamento dos taludes marginais a partir da instrumentação em seções localizadas no Perímetro Irrigado Cotinguib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
4
Order By: Relevance
“…A distribuição da erosão marginal pode variar de um ponto para o outro devido as características morfológicas e sedimentológicas do talude (Holanda et al, 2007), associados com as variações da velocidade da corrente, considerando que a velocidade é menor próximo às margens (Carvalho, 1994).…”
Section: Caracterização Do Processo De Erosão Das Margens Do Rio Miraunclassified
“…A distribuição da erosão marginal pode variar de um ponto para o outro devido as características morfológicas e sedimentológicas do talude (Holanda et al, 2007), associados com as variações da velocidade da corrente, considerando que a velocidade é menor próximo às margens (Carvalho, 1994).…”
Section: Caracterização Do Processo De Erosão Das Margens Do Rio Miraunclassified
“…According to Casado et al (2002), this causes the water depth to remain at the same level for long periods since the force of the current has increased effects on the bank at that level and promotes the removal of soil particles. Holanda et al (2007) explains that riverbank erosion along the lower course of the São Francisco River occurs primarily under normal day-to-day conditions even without destructive floods or other weather events; further, the author concludes that it is possible to observe the magnitude of the erosion process and retreat of the bank within a few days itself. Coops et al (1996) compared the effects of waves on artificial streams in the case of treatments with and without the protective vegetation and concluded that the erosion values for the unprotected banks were higher.…”
Section: Introductionmentioning
confidence: 98%
“…Martins et al [7] report that the dams built along the SF river in the LSF sub region condition the volume of flow in the region of the SF river, and Barros [8] reports the Sobradinho Dam has changed the entire balance of the LSF's floodplains, thus extremely affecting human activities, linked to the river´s cycles. Environmental effects such as the modification of the river´s regime, the solid particles in suspension [9], erosive processes in its right bank in the Lower San Francisco Sergipano's (LSFS) section [10], the acceleration of marginal erosion, altering the landscape towards the "Irrigated Perimeters", endangerment of agricultural areas, restriction of idle areas resulting in loss of agricultural areas [11] are common in these locations. The environmental impact on wildlife, loss of harvests due to rodent outbreaks, water distribution shortages in the "Irrigated Perimeters" and technical assistance scarcity are some of the issues faced by the farmers in the LSFS.…”
Section: Introductionmentioning
confidence: 99%